Characterization of XR‐RV3 GafChromic® films in standard laboratory and in clinical conditions and means to evaluate uncertainties and reduce errors. Issue 7 (17th June 2015) - Farah, J.; Trianni, A.; Ciraj‐Bjelac, O.; Clairand, I.; De Angelis, C.; Delle Canne, S.; Hadid, L.; Huet, C.; Jarvinen, H.; Negri, A.; Novák, L.; Pinto, M.; et al.
Abstract : Purpose: To investigate the optimal use of XR‐RV3 GafChromic ® films to assess patient skin dose in interventional radiology while addressing the means to reduce uncertainties in dose assessment. Methods: XR‐Type R GafChromic films have been shown to represent the most efficient and suitable solution to determine patient skin dose in interventional procedures. As film dosimetry can be associated with high uncertainty, this paper presents the EURADOS WG 12 initiative to carry out a comprehensive study of film characteristics with a multisite approach. The considered sources of uncertainties include scanner, film, and fitting‐related errors. The work focused on studying film behavior with clinical high‐dose‐rate pulsed beams (previously unavailable in the literature) together with reference standard laboratory beams. Results: First, the performance analysis of six different scanner models has shown that scan uniformity perpendicular to the lamp motion axis and that long term stability are the main sources of scanner‐related uncertainties. These could induce errors of up to 7% on the film readings unless regularly checked and corrected. Typically, scan uniformity correction matrices and reading normalization to the scanner‐specific and daily background reading should be done. In addition, the analysis on multiple film batches has shown that XR‐RV3 films have generally good uniformity within one batch (<1.5%), require 24 h to stabilize after the irradiation and their response is roughly independent of dose rate (<5%). However, XR‐RV3 films showed large variations (up to 15%) with radiation quality both in standard laboratory and in clinical conditions. As such, and prior to conducting patient skin dose measurements, it is mandatory to choose the appropriate calibration beam quality depending on the characteristics of the x‐ray systems that will be used clinically. In addition, yellow side film irradiations should be preferentially used since they showed a lower dependence on beam parameters compared to white side film irradiations. Finally, among the six different fit equations tested in this work, typically used third order polynomials and more rational and simplistic equations, of the form dose inversely proportional to pixel value, were both found to provide satisfactory results. Fitting‐related uncertainty was clearly identified as a major contributor to the overall film dosimetry uncertainty with up to 40% error on the dose estimate. Conclusions: The overall uncertainty associated with the use of XR‐RV3 films to determine skin dose in the interventional environment can realistically be estimated to be around 20% ( k = 1). This uncertainty can be reduced to within 5% if carefully monitoring scanner, film, and fitting‐related errors or it can easily increase to over 40% if minimal care is not taken. This work demonstrates the importance of appropriate calibration, reading, fitting, and other film‐related and scan‐related processes, which will help improve the accuracy of skin dose measurements in interventional procedures.